Strategic Marketing Approaches For Automotive Industries : A Literature Review Study - Anggi Rizki Muharram; Febriansyah Febriansyah; Ahmad Azmy (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to analyze the marketing strategies employed by the Indonesian automotive industry in response to the era of disruption. Through a comprehensive literature review, this research identifies current trends in the automotive industry, including the adoption of digital technologies, changing consumer behavior, and global competition. The findings reveal that the Indonesian automotive industry has undertaken various efforts to enhance competitiveness, such as product innovation, export market expansion, and the implementation of digital technologies. However, challenges persist, including intensifying competition and shifting consumer preferences. This study concludes that to remain relevant, the Indonesian automotive industry needs to continuously adapt to market changes and strengthen digital marketing strategies.